Optimization of the Curvature Radius Coefficient of RV Reducer Main Bearing based on ADAMS - Zhu Bingfeng; Lei Xiaochun (Jixie chuandong)
The main bearing of RV reducer is studied. Firstly,the contact stress and elastic deformation of bearing with different curvature radius coefficient are calculated by using the MATLAB. Secondly,the dynamics analysis of the contact force of ball and bearing inner and outer ring is carried out by using the impact function in ADAMS software. By using the method of analysis and comparison the ball bearing which has different radius curvature coefficient,among transient impact force,steady contact force and the distribution of contact force of the forward radius force. Through the comparison and analysis,the better radius curvature coefficient is selected for the RV reducer main bearing.